Effective Emission Heights of Various OH Lines From X‐Shooter and SABER Observations of a Passing Quasi‐2‐Day Wave. Issue 24 (23rd December 2022) - Noll, S.; Schmidt, C.; Kausch, W.; Bittner, M.; Kimeswenger, S.
Abstract: Chemiluminescent radiation of the vibrationally and rotationally excited hydroxyl (OH) radical, which dominates the nighttime near‐infrared emission of the Earth's atmosphere in wide wavelength regions, is an important tracer of the chemical and dynamical state of the mesopause region between 80 and 100 km. As radiative lifetimes and rate coefficients for collision‐related transitions depend on the OH energy level, line‐dependent emission profiles are expected. However, except for some height differences for whole bands mostly revealed by satellite‐based measurements, there is a lack of data for individual lines. We succeeded in deriving effective emission heights for 298 OH lines thanks to the joint observation of a strong quasi‐2‐day wave (Q2DW) in eight nights in 2017 with the medium‐resolution spectrograph X‐shooter at the Very Large Telescope at Cerro Paranal in Chile and the limb‐sounding SABER radiometer on the TIMED satellite. Our fitting procedure revealed the most convincing results for a single wave with a period of about 44 hr and a vertical wavelength of about 32 km. The line‐dependent as well as altitude‐resolved phases of the Q2DW then resulted in effective heights which differ by up to 8 km and tend to increase with increasing vibrational and rotation excitation. The measured dependence of emission heights and wave amplitudes (which were strongest after midnight) on the line parameters implies the presence of a cold thermalized and a hot non‐thermalized population for each vibrational level. Plain Language Summary: Hydroxyl (OH) is an important molecule in the Earth's atmosphere at altitudes between 80 and 100 km. It is the main source of atmospheric nighttime radiation in the near‐infrared wavelength range and is therefore a valuable tracer of the chemistry and dynamics at high altitudes. The emission spectrum consists of various lines which are related to different levels of vibration and rotation. Although the vertical emission distribution should depend on the given line due to differences in the deactivation of the corresponding energy levels, the line‐specific details have been uncertain until now. We have succeeded in deriving effective time‐averaged emission heights for 298 OH lines based on the combination of ground‐based line‐resolved and space‐based height‐resolved observations of a very strong rising wave with a period close to 2 days and a relatively short vertical wavelength in eight nights in 2017. The resulting heights (obtained via the line‐dependent wave phases) differ by up to 8 km and generally increase with higher molecular vibration and rotation. They are valuable for ground‐based studies of other waves and contribute (combined with conclusions from the wave amplitudes) to a better understanding of the internal processes in OH molecules. Key Points: X‐shooter‐based intensities of 298 hydroxyl (OH) lines from eight nights show a strong quasi‐2‐day wave (Q2DW) in southern summer 2017 Fits of the Q2DW phase in the X‐shooter data and Sounding of the Atmosphere using Broadband Emission Radiometry‐based OH emission profiles were used to derive effective OH emission heights The line‐dependent wave amplitudes confirm the presence of cold and hot OH populations for each vibrational level